Towards the ethical librarian: Perspectives and challenges of staff of Sam Jonah Library, University of Cape Coast – Ghana. Issue 6 (12th August 2019) - Amoah, Gloria Bosomtwi; Yeboah, Eugene Baah
Abstract : Purpose: The purpose of this paper is to examine the perspectives and viewpoints of professional staff of the Sam Jonah Library in as much as the ethical aspects of their profession are concerned. The paper also seeks to determine the common ethical issues that confront these professionals and their default courses of action in dealing with these issues. Design/methodology/approach: The descriptive survey design was used as the research methodology with the population of the study being all professional (post-graduate diploma and above) and para-professional (certificate, diploma and first degree) staff of the library. Due to the small number of professional staff (43) in the library, the census sampling technique was used. Findings: Results indicated the existence of ethical dilemmas in the working lives of these professionals with guidance for dealing with these dilemmas emanating mostly from consultation of senior colleagues. Although the findings showed that the Ghana Library Association (GLA) had an ethics handbook, it was revealed that majority of the staff were not aware of its existence. It was also discovered that one of the major challenges of these professionals is the absence of a specific library code of ethics handbook to guide staff in case they are confronted with these ethical dilemmas. The study recommends a strong awareness creation initiative from the GLA to bring to the notice of members, the existence of a formal code of ethics document. Originality/value: The paper provides information on specific ethical issues confronting staff of the library and their current modes of dealing with the dilemmas they encounter.